Personal agency - empowerment in beneficiaries of program juntos, Ayacucho - García Vargas, Betty (2020)
The present study aimed identify the level of personal agency and empowerment in the beneficiaries of the program Juntos from Vilcashuaman - Ayacucho. The research is of descriptive comparative design. The sample consisted of 320 beneficiary between which have less two years and more three years into the program Juntos. The instrument was Personal Agency and Empowerment Scale of Pick (2007). The results concluded that personal agency increase according the time and empowerment shows no difference from one group to another. Research is recommended to reproduce in order to deepen and analyze the features involved in this type of population.